Antibodies to acetylcholine receptor in parous women with myasthenia: evidence for immunization by fetal antigen. - Matthews, I; Sims, G; Ledwidge, S; Stott, D; Beeson, D; Willcox, N; Vincent, A (2002)
The weakness in myasthenia gravis (MG) is mediated by autoantibodies against adult muscle acetylcholine receptors (AChR) at the neuromuscular junction; most of these antibodies also bind to fetal AChR, which is present in the thymus. In rare cases, babies of mothers with MG, or even of asymptomatic mothers, develop a severe developmental condition, arthrogryposis multiplex congenita, caused by antibodies that inhibit the ion channel function of the fetal AChR while not affecting the adult AChR. Here we show that these fetal AChR inhibitory antibodies are significantly more common in females sampled after pregnancy than in those who present before pregnancy, suggesting that they may be induced by the fetus. Moreover, we were able to clone high-affinity combinatorial Fab antibodies from thymic cells of two mothers with MG who had babies with arthrogryposis multiplex congenita. These Fabs were highly specific for fetal AChR and did not bind the main immunogenic region that is common to fetal and adult AChR. The Fabs show strong biases to VH3 heavy chains and to a single Vkappa1 light chain in one mother. Nevertheless, they each show extensive intraclonal diversification from a highly mutated consensus sequence, consistent with antigen-driven selection in successive steps. Collectively, our results suggest that, in some cases of MG, initial immunization against fetal AChR is followed by diversification and expansion of B cells in the thymus; maternal autoimmunity will result if the immune response spreads to the main immunogenic region and other epitopes common to fetal and adult AChR.